Effect of sub-micron grains and defect-dipole interactions on dielectric properties of iron, cobalt, and copper doped barium titanate ceramics - Mills, Sara C.; Patterson, Eric A.; Staruch, Margo L. (Frontiers in Chemistry, 2023)
Dilutely doped ferroelectric materials are of interest, as engineering these materials by introducing point defects via doping often leads to unique behavior not otherwise achievable in the undoped material. For example, B-site doping with transition metals in barium titanate (BaTiO3, or BTO) creates defect dipoles via oxygen vacancies leading enhanced polarization, strain, and the ability to tune dielectric properties. Though defect dipoles should lead to dielectric property enhancements, the effect of grain size in polycrystalline ferroelectrics such as BTO plays a significant role in those properties as well. Herein, doped BTO with 1.0% copper (Cu), iron (Fe), or cobalt (Co) was synthesized using traditional solid-state processing to observe the contribution of both defect-dipole formation and grain size on the ferroelectric and dielectric properties. 1.0% Cu doped BTO showed the highest polarization and strain (9.3 µC/cm 2 and 0.1%, respectively of the three doped BTO samples. While some results, such as the aforementioned electrical properties of the 1.0% Cu doped BTO can be explained by the strong chemical driving force of the Cu atoms to form defect dipoles with oxygen vacancies and copper's consistent +2 valency leading to stable defect-dipole formation (versus the readily mixed valency states of Fe and Co at +2/+3), other properties cannot. For instance, all three Tc values should fall below that of undoped BTO (typically 120-135°C), but the Tc of 1.0% Cu BTO actually exceeds that range (139.4°C). Data presented on the average grain size and distribution of grain sizes provides insight allowing us to decouple the effect of defect dipoles and the effect of grain size on properties such as Tc, where the 1.0% Cu BTO was shown to possess the largest overall grains, leading to its increase in Tc. Overall, the 1% Cu BTO possessed the highest polarization, strain, and Tc and is a promising dopant for engineering the performance of the material. This work emphasizes the challenge of extricating one effect (such as defect-dipole formation) from another (grain size modification) inherent to doping polycrystalline BTO.